Understanding the Mechanism and Selectivities of the Reaction of Meta-Chloroperbenzoic Acid and Dibromocarbene with β-Himachalene: A DFT Study - Sana El Hamidi; Malika Khnifira; El Mokhtar Lemdek; Redouan Hammal; Noureddine Barka; M’hamed Sadiq; Ahmed Benharref; Ahmed Chekroun; Hssaine Zgou; Mohamed Abdennouri (Heteroatom Chemistry)
This study was performed to understand the site selectivity in the reaction between β-himachalene and meta-chloroperbenzoic acid (m-CPBA) in the first step followed by the addition of dibromocarbene (CBr2) to the main monoepoxidation product Pα formed in the first reaction. Calculations were performed using the Becke three-parameter hybrid exchange functional and the Lee–Yang–Parr correlation functional (B3LYP) with the 6-311 + G (d, p) basis set. Transition states were located by QST2, and their highlighting was validated by the existence of only one imaginary frequency in the Hessian matrix. The action of m-CPBA on β-himachalene was analyzed on the two double bonds of β-himachalene whose theoretical calculations show that the attack affects the most substituted double bond on α side containing hydrogen of ring junction. The obtained Pα product thereafter treated with dibromocarbene leads via an exothermic reaction to the six-membered ring double bond position of α-monoepoxide. The major products Pαα are kinetically and thermodynamically favored with a high stereoselectivity in perfect correlation with the experimental observations.